Operational semantics for declarative multi-paradigm languages - Albert, Elvira; Hanus, Michael; Huch, Frank; Oliver, Javier; Vidal, Germán (Journal of symbolic computation, 2005)
Declarative multi-paradigm languages combine the most important features of functional, logic and concurrent programming. The computational model of such integrated languages is usually based on a combination of two different operational principles: narrowing and residuation. This work is motivated by the fact that a precise definition of an operational semantics including all aspects of modern multi-paradigm languages like laziness, sharing, non-determinism, equational constraints, external functions and concurrency does not exist. Therefore, in this article, we present the first rigorous operational description covering all the aforementioned features in a precise and understandable manner. We develop our operational semantics in several steps. First, we define a natural (big-step) semantics covering laziness, sharing and non-determinism. We also present an equivalent small-step semantics which additionally includes a number of practical features like equational constraints and external functions. Then, we introduce a deterministic version of the small-step semantics which makes the search strategy explicit; this is essential for profiling, tracing, debugging etc. Finally, the deterministic semantics is extended in order to cover the concurrent facilities of modern declarative multi-paradigm languages. The semantics developed provides an appropriate foundation for modeling actual declarative multi-paradigm languages like Curry. The complete operational semantics has been implemented and used with various programming tools.